CDK12 INHIBITION REVERSES DE NOVO AND ACQUIRED PARP INHIBITOR RESISTANCE IN BRCA WILD-TYPE AND MUTATED MODELS OF TRIPLE-NEGATIVE BREAST CANCER - Johnson, Shawn F. (Cell Rep, 2016)
Although poly (ADP-ribose) polymerase (PARP) inhibitors are active in homologous recombination (HR)-deficient cancers, their utility is limited by acquired resistance following restoration of HR. Here, we report that dinaciclib, an inhibitor of cyclin-dependent kinases (CDKs) 1, 2, 5 and 9, additionally has potent activity against CDK12, a transcriptional regulator of HR. In BRCA-mutated triple-negative breast cancer (TNBC) cells and patient-derived xenografts (PDXs), dinaciclib ablates restored HR and reverses PARP inhibitor resistance. Additionally, we show that de novo resistance to PARP inhibition in BRCA1-mutated cell lines and a PDX derived from a PARP inhibitor-naïve BRCA1 carrier is mediated by residual HR and is reversed by CDK12 inhibition. Finally, dinaciclib augments the degree of response in a PARP inhibitor-sensitive model, converting tumor growth inhibition to durable regression. These results highlight the significance of HR disruption as a therapeutic strategy and support the broad use of combined CDK12 and PARP inhibition in TNBC.